2020
DOI: 10.21153/jtlge2020vol11no1art921
|View full text |Cite
|
Sign up to set email alerts
|

Employability initiatives in undergraduate education and application to human nutrition: A scoping review

Abstract: Human nutrition is a growing field with an increasing job market and high demand for university study, yet graduates report feeling underprepared for and unaware of potential job opportunities. This scoping review aimed to identify employment initiatives used in undergraduate programs to support an evidence-based approach to the development of future initiatives for human nutrition courses. The scoping review following PRISMA-ScR criteria was initially conducted in October 2018 and updated in April 2020. Searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Croxford et al 12 reported that industry stakeholders perceived the sourcing of WIL opportunities as a responsibility of the university curricula. However, our survey found that many respondents had to self‐source their work experiences, most likely because work placement in nutrition science degrees is not a standard offering as it is with other disciplines 21,22 . This finding could suggest that the work experience activities undertaken were insufficiently tailored to the scope of nutrition practice or did not showcase the diverse range of roles that graduates can hold.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Croxford et al 12 reported that industry stakeholders perceived the sourcing of WIL opportunities as a responsibility of the university curricula. However, our survey found that many respondents had to self‐source their work experiences, most likely because work placement in nutrition science degrees is not a standard offering as it is with other disciplines 21,22 . This finding could suggest that the work experience activities undertaken were insufficiently tailored to the scope of nutrition practice or did not showcase the diverse range of roles that graduates can hold.…”
Section: Discussionmentioning
confidence: 89%
“…Engaging with industry through WIL offers nutrition science students insight into potential career options 21 . Career development and WIL were listed in the top‐five professional skills that graduates both valued or would have valued but did not get in their nutrition course.…”
Section: Discussionmentioning
confidence: 99%
“…Becoming a job ready graduate requires awareness of the worlds-of-work so students can align their interests and energies toward appropriate career choices (McIlveen et al, 2011). A scoping review by Murray et al (2020) of employability initiatives incorporated into undergraduate degree courses found work-based placements were most common and project-based industry collaboration had the highest student and employer satisfaction. These initiatives expose students to real-world scenarios and support professional network development; they are also labour intensive to administer and sustain and it is challenging to source placements for courses that lead to a wide range of jobs.…”
Section: Introductionmentioning
confidence: 99%
“…
For a qualified nutritionist to obtain registration with the Nutrition Society of Australia they must first demonstrate that they meet a set of competencies relating to required nutrition knowledge and skills (1) . However, theoretical knowledge and a technical skillset may not be enough to actively contribute to the workforce as a new graduate (2) . Employers have previously expressed a desire for nutrition graduates to also develop employability skills in undergraduate studies to be better prepared for the workforce (3) .
…”
mentioning
confidence: 99%